In Vivo and Impression Cytology Study on the Effect of Compatible Solutes Eye Drops on the Ocular Surface Epithelial Cell Quality in Dry Eye Patients. (29th June 2015) - Lanzini, Manuela; Curcio, Claudia; Colabelli-Gisoldi, Rossella Annamaria; Mastropasqua, Alessandra; Calienno, Roberta; Agnifili, Luca; Nubile, Mario; Mastropasqua, Leonardo
Abstract : The aim of this study is to investigate in vivo and ex vivo ocular surface alterations induced by dry eye disease and modification after osmoprotective therapy. Forty-eight eyes of 24 patients suffering from dry eye have been recruited. All patients received Optive (compatible solutes) eye drops in one randomly selected eye and Hylogel (sodium hyaluronate 0, 2%) in the other. Follow-up included a baseline visit and further examination 30-, 60-, and 90-day intervals (which comprises clinical evaluation, in vivo confocal microscopy—IVCM—of the ocular surface, and conjunctival impression cytology). No significant difference in Schirmer I Test, TBUT, and vital staining results was observed during the follow-up period in both groups. IVCM showed in all patients an improvement of ocular surface epithelial morphology and signs of inflammation (oedema and keratocyte activation). However, these modifications were more evident in patients treated with Optive therapy. A significant reduction of the expression of MMP9 and IL6 in Optive group was observed during the follow-up period in comparison to Hylogel treatment. Our results show that in dry eye disease therapy based on osmoprotective eye drops determines a reduction of inflammatory activation of ocular surface, with consequent improvement of the quality of corneal and conjunctival epithelium.